A new approach of progressive freeze concentration in removing of 2, 4, 6 trichlorophenol from wastewater: effect of coolant temperature & optimization studies by using response surface methodology (RSM): article - Jamal Ikhsana, Ikhmal Zariq Al Imran; Mazzam, Anwar Addini; Bakar, Muhamad Noor Faqeh; Hamizlan, Hariz Asyraf; Ab. Hamid, Farah Hanim (2020)
2,4,6-Trichlorophenolx(TCP) is a poisonous, carcinogenic andxmutagenic pollutantxthat is characterize as a clear and colourless liquid, have strong odour like trichloroethylene or chloroform. 2,4,6-TCP has been classified as one of the primary pollutants as enacted by the Department of Environment (DOE). According to Malaysia in Environmental Quality Act 1979 (Sewage and Industrial Effluent), it should be treated to be less than 1 ppm for inland water discharge. The aim of this paper is to study the effect of coolant temperature on the performance of progressive freeze concentration (PFC) in removing 2,4,6 TCP from wastewater. This paper also aims to obtain the optimum coolant temperature and circulation flowrate for better performance of PFC using Response Surface Methodology. By conducting experiment to study thexeffectxof coolant temperature towards PFC performance, it was found that low K value and high TR was obtained at -6°C. According to the ANOVA analysis, PFC system was predicted to be able to produce low K value at 0.15 at -4.5°C of coolant temperature and 1255 rpm of circulation flowrate. The analysis also predicted that the PFC able to produce TR as high as 84.8% at -5°C of coolant temperature and 862 rpm of circulation flowrate.